2009
DOI: 10.1152/ajprenal.90682.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of multiple phosphorylation sites in the COOH-terminal tail of aquaporin-2 for water transport: evidence against channel gating

Abstract: Moeller HB, MacAulay N, Knepper MA, Fenton RA. Role of multiple phosphorylation sites in the COOH-terminal tail of aquaporin-2 for water transport: evidence against channel gating. Am J Physiol Renal Physiol 296: F649 -F657, 2009. First published January 14, 2009 doi:10.1152/ajprenal.90682.2008.-Arginine vasopressin (AVP)-regulated phosphorylation of the water channel aquaporin-2 (AQP2) at serine 256 (S256) is essential for its accumulation in the apical plasma membrane of collecting duct principal cells. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 34 publications
5
56
0
Order By: Relevance
“…11,12 The absence of any effect of CT on trafficking of an AQP2(S256A) mutant in LLC-PK1 cells confirms that phosphorylation of S256 is essential for AQP2 membrane accumulation in response to CT as well as VP. 11,12 At present, the effect of CT on phosphorylation of other target residues in the AQP2 protein 52,53 is not known. The mechanism regulating AQP2 trafficking upon CT and VP binding to their respective receptors seems similar; CT signals mainly via cAMP in the nephron, 40,42 whereas VP affects both intracellular cAMP and calcium levels, and increased intracellular calcium has been implicated in the response to VP 54 including AQP2 trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The absence of any effect of CT on trafficking of an AQP2(S256A) mutant in LLC-PK1 cells confirms that phosphorylation of S256 is essential for AQP2 membrane accumulation in response to CT as well as VP. 11,12 At present, the effect of CT on phosphorylation of other target residues in the AQP2 protein 52,53 is not known. The mechanism regulating AQP2 trafficking upon CT and VP binding to their respective receptors seems similar; CT signals mainly via cAMP in the nephron, 40,42 whereas VP affects both intracellular cAMP and calcium levels, and increased intracellular calcium has been implicated in the response to VP 54 including AQP2 trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…8 Phosphorylation of AQP2 at S264 and S269 requires prior phosphorylation of S256. 9 Immunohistochemistry showed that pS269-AQP2 localizes exclusively in the apical plasma membrane of the connecting tubule and CD. 8,10 AVP-stimulated AQP2 phosphorylation thus induces plasma membrane accumulation and retention of the channel.…”
mentioning
confidence: 98%
“…8 Phosphorylation of AQP2 at S264 and S269 requires prior phosphorylation of S256. 9 Immunohistochemistry showed that pS269-AQP2 localizes exclusively in the apical plasma …”
mentioning
confidence: 99%
“…Preparation of Oocyte Membranes and Western Blot-Purified oocyte membranes were obtained as previously described (26). In brief, oocytes expressing PICK1 and/or GLT1 were homogenized in 1 ml of buffer (HbAϩ: 5 mM MgCl 2 , 5 mM NaH 2 PO 4 , 1 mM EDTA, 80 mM sucrose, 20 mM Tris, pH 7.4, 8 M leupeptin, and 0.4 mM Pefabloc).…”
Section: Methodsmentioning
confidence: 99%